The First Reported Case of Pulmonary Embolism and Deep Vein Thrombosis Associated with Intraductal Papillary Mucinous Neoplasm: A Case Report (International Journal of Clinical Research, 2023)
Background: Reported cases of Intraductal papillary mucinous neoplasm (IPMN) are becoming more and more frequent. The risk of hypercoagulability associated with IPMN is not clearly established in the literature as it was only reported in four cases. Therefore, we present a unique case of a patient with IPMN who subsequently developed acute pulmonary embolism (PE) and deep venous thrombosis (DVT). Case presentation: A 70-year-old healthy female patient complained of palpitation, chest pain, and dyspnea at rest. She had normal vital signs and findings on physical examination. Laboratory tests showed an increase in the D-Dimer level of 3,730 ng/mL fibrinogen equivalent unit (FEU). Bilateral DVT ultrasound (DVT-US) of the lower extremities was positive for acute calf DVT in the right lower extremity involving the soleal vein. CT-PE chest with IV contrast was remarkable for segmental and subsegmental pulmonary arteries thrombosis. She was started on a heparin drip and then transitioned to rivaroxaban for the treatment of PE and DVT. She was discharged in stable condition with outpatient follow-up. Conclusion: IPMN of the pancreas is an exocrine pancreatic neoplasm often detected on Computed Tomography (CT) scan or Magnetic Resonance Imaging (MRI). It is usually non-malignant but was found to be more prone to progress into cancer in contrast to the other types of pancreatic cysts. An increased risk of hypercoagulability with pre-malignant pancreatic lesions such as IPMN has not yet been well established. As far as we know, this case report is the first article presenting IPMN associated with both acute DVT and PE in a relatively healthy individual with no prior risk factor for hypercoagulability. Although there is scattered evidence suggesting an increased risk of thromboembolic events with IPMN, this unique case of DVT and PE associated with IPMN highlights the importance of close monitoring of these patients, especially those who have risk factors for thrombosis.